2023
DOI: 10.3390/metabo13101048
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Trace Metal Elements and Glucose Metabolism: Evidence from Zinc, Copper, Iron, and Manganese-Mediated Metabolic Regulation

Zhendong Sun,
Yuzhuo Shao,
Kunhao Yan
et al.

Abstract: Trace metal elements are of vital importance for fundamental biological processes. They function in various metabolic pathways after the long evolution of living organisms. Glucose is considered to be one of the main sources of biological energy that supports biological activities, and its metabolism is tightly regulated by trace metal elements such as iron, zinc, copper, and manganese. However, there is still a lack of understanding of the regulation of glucose metabolism by trace metal elements. In particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 167 publications
0
2
0
Order By: Relevance
“…Although high serum Cu level is widely associated with type 2 diabetes and metabolic syndrome [47][48][49], there is little evidence related to the association with IR. However, previous studies have shown a positive association between serum Cu levels and IR in children and adult populations [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Although high serum Cu level is widely associated with type 2 diabetes and metabolic syndrome [47][48][49], there is little evidence related to the association with IR. However, previous studies have shown a positive association between serum Cu levels and IR in children and adult populations [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrates are important macronutrients that provide energy and nutrients to the body, and they are categorized into simple sugars, complex carbohydrates, and glycoconjugates based on their structures [55]. Carbohydrates, predominantly glucose, are initially and most rapidly utilized during periods of energy shortage, which makes them the primary source of biological energy in living organisms [56]. It is critical to maintain glucose levels around 5.5 mM in the blood.…”
Section: Discussionmentioning
confidence: 99%